Experience of Spiritual Dryness and Acedia Symptoms in Seventh-Day Adventists - Büssing, Arndt (Journal of religion and health, 2021)
In a cross-sectional survey among 626 Adventists, we investigated their perception of spiritual dryness, and its association with indicators of Acedia, well-being and emotional exhaustion. Women, younger persons and those without a specific duty within the church had significantly higher spiritual dryness scores. Spiritual dryness was predicted best by perceived Excessive Spiritual Demands (indicating spiritual exhaustion) and low perception of the sacred. Further predictors are Acedia’s Difficulties in Prayer Life, reduced well-being and emotional exhaustion. The underlying causes might be complex and thus to support persons experiencing these phases, a thorough differentiation of the underlying ‘spirits’ is required.